2021
DOI: 10.1101/2021.04.02.438171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Native or non-native protein-protein docking models? Molecular dynamics to the rescue

Abstract: Molecular docking excels at creating a plethora of potential models of protein-protein complexes. To correctly distinguish the favourable, native-like models from the remaining ones remains, however, a challenge. We assessed here if a protocol based on molecular dynamics (MD) simulations would allow to distinguish native from non-native models to complement scoring functions used in docking. To this end, first models for 25 protein-protein complexes were generated using HADDOCK. Next, MD simulations complement… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…Previous studies showed that the trends that allow to differentiate between native and nonnative complexes are already evident within the first 5 ns, and are only augmented during the rest of the simulation. 64 Our analysis of the trajectory during the 50 ns simulation showed limited variation in the epitopic region and emphasized the stability of the Van der Waal contacts established by L313, which are central for the functional KD035 complex formation. On the other hand, marginal H-bond and salt bridge mediated interactions showed a greater instability.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Previous studies showed that the trends that allow to differentiate between native and nonnative complexes are already evident within the first 5 ns, and are only augmented during the rest of the simulation. 64 Our analysis of the trajectory during the 50 ns simulation showed limited variation in the epitopic region and emphasized the stability of the Van der Waal contacts established by L313, which are central for the functional KD035 complex formation. On the other hand, marginal H-bond and salt bridge mediated interactions showed a greater instability.…”
Section: Discussionmentioning
confidence: 73%
“…[61][62][63] Understandably, the inherent flexibility of each monomer contributes to the energy landscape of the complex. 61 MD simulations are frequently utilized as a means to complement the information obtained by static analysis of protein-protein docking 64 and also to correct errors in the crystal structure mainly due to packing forces. The inspection of the symmetry mates for our B1 and KD035 structures show no involvement in the packing interfaces of the CDR loops or areas which could otherwise affect their conformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each of the four selected ACE2-interactor complexes, we performed a 100 ns long molecular dynamics simulation. The aim of this procedure is both to refine the predicted docking model [ 47 , 48 ] and to statistically study the structural stability of the estimated complex by analyzing the inter-molecular interactions during the simulation. Indeed, the greater the stability of the interaction between the ACE2 receptor and the corresponding molecular partner (each of the 4 selected), the greater the probability that the two macromolecules interact with high-affinity [ 16 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…For both complexes, we monitored the number of inter-chain hydrogen bonds (H-bonds), buried surface area (BSA) and interface R.M.S.D. (iRMSD) relative to the starting model, as these parameters were recently shown to be useful in discriminating native from non-native docked models by MD (Jandova, Vargiu et al 2021 (Figure 5C). Consistent with our modeling results, ACKR1 Cys51 was previously identified by mutagenesis as critical for LukED intoxication of erythrocytes (Spaan, Reyes-Robles et al 2015), as well as LukE loops 1, 3 and 4 (Peng, Takeshita et al 2018, Vasquez, Lubkin et al 2020.…”
Section: Simulations Of Ackr1-luke Docked Model Identify Site 1 As the Major Sulfotyrosine Binding Pocket For Ackr1 N-terminal Peptidementioning
confidence: 99%